Introduction to Access 2007 - Miles, Timothy; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"This course covers the basic functions and features of Access 2007. Students will learn how to design and create databases; work with tables, fields, and records; sort and filter data; and create queries, forms, and reports. Designated as Approved Courseware for the Microsoft Certified Application Specialist program, this course will help students prepare for the Access 2007 exam (77-605). For comprehensive certification training, students should complete Access 2007: Introduction, Intermediate, and Advanced."--Resource description page.
Title from title screen (Safari, viewed October 28, 2016).
Release information from resource description page (Safari, viewed October 28, 2016).
Presenter, Timothy Miles.
Keywords: Microsoft Access; Database management; Electronic books